Preventive Medicine in General Practice: An Evaluation of the Consultations of Ten General Practitioners - Williams, Jonathan (Clinical Press, 1988)

(untitled) (Bristol Med Chir J)
Ten final year medical students observed 360 consultations undertaken by 10 West Country General Practitioners. In 31% of the consultations, General Practitioners initiated preventive medical care. These consultations lasted 1.5 minutes longer than those in which no preventive measures were initiated, and most patients reacted with interest or enthusiasm to the preventive care. In 11% of the consultations patients themselves sought preventive advice. These consultations were not significantly longer than consultations in which patients sought only more immediate help or symptom relief. General Practitioners reacted favourably to 85% of the preventive enquiries.